2022
DOI: 10.3390/math10030429
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Correlation and Regression Analyses in Estimating a Functional Relationship of Digitalization Factors

Abstract: Digitalization processes affect all levels and spheres of human activities, from personal communications to public events. The widespread implementation of digital technologies has an ambiguous effect on the personal, social, and economic paths of modern society’s development. At the moment, there is no single approach to the estimation of digitalization’s impact, particularly on the financial and economic properties of a company. The objective of this study was to create multiple models for the assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…The research outcomes provide insights for policy-makers (in the industry and social arena) on the societal impact of digital transformation on challenges. The positive impacts and the various advantages of digitalization to business and our daily lives are also reported in other studies (Hinterhuber, 2022;Zemlyak et al, 2022). The Abu Dhabi study showed a direct association of the positive impact variable with our happiness and subjective health.…”
Section: B Discussionsupporting
confidence: 73%
“…The research outcomes provide insights for policy-makers (in the industry and social arena) on the societal impact of digital transformation on challenges. The positive impacts and the various advantages of digitalization to business and our daily lives are also reported in other studies (Hinterhuber, 2022;Zemlyak et al, 2022). The Abu Dhabi study showed a direct association of the positive impact variable with our happiness and subjective health.…”
Section: B Discussionsupporting
confidence: 73%
“…Green Performance Management (GPM) displayed a positive and significant relationship with the Environmental Consciousness (EC) (β = 0.289), and Green Training (GT) had significant relationship with Environmental Consciousness (EC) (β = 0.649) in Archroma and Farhan Pharmaceuticals companies located in Jamshoro and Kotri, Karachi, Sindh, Pakistan. β coefficients measure multiple correlations of exogenous and endogenous factors (Zemlyak et al, 2022). According to Hair et al (2010), values for t that are significant are 2.58 (p < 0.01), 1.96 (p < 0.05), 1.64 (p < 0.10), and 2.326 (p < 0.01).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Однако, период пандемии и постпандемические последствия вынудили организаций максимально быстро адаптироваться к новым условиям ведения бизнеса, значительно увеличив расходы на цифровизацию деятельности компаний. Те организации, которые быстро отреагировали на внешние угрозы, смогли адаптироваться и продолжить свой бизнес; компании, не уделявшие должного внимания процессам цифровых трансформаций и оказания услуг (выпуска продукции) в новом формате, либо потерпели значительные убытки, либо прекратили существование [14].…”
Section: можно выделить следующие функции электронного правительстваunclassified